Strategies to improve patient care for obstructive sleep apnea: a report from the American Academy of Sleep Medicine Sleep-Disordered Breathing Collaboration Summit - Rosen, Ilene M. (J Clin Sleep Med, 2020)
In Chicago, Illinois, on Saturday, November 10, 2018, the American Academy of Sleep Medicine hosted 35 representatives from 14 medical societies, nurse practitioner associations and patient advocacy groups for a one-day Sleep-Disordered Breathing Collaboration Summit to discuss strategies to improve the diagnosis and treatment of obstructive sleep apnea. This report provides a brief synopsis of the meeting, identifies current challenges, and highlights potential opportunities for ongoing collaboration. CITATION: Rosen IM, Rowley JA, Malhotra RK, Kristo DA, Carden KA, Kirsch DB. Strategies to improve patient care for obstructive sleep apnea: a report from the American Academy of Sleep Medicine Sleep-Disordered Breathing Collaboration Summit. J Clin Sleep Med. 2020;16(11):1933–1937.